Analisis Pengaruh Sektor Pariwisata terhadap Penyerapan Tenaga Kerja di Provinsi Kalimantan Barat Periode 2018–2023 - Novi Ramadhani; Fatimah Fatimah; Reni Helvira (Lembaga Yasin AlSys, 2025)
The low contribution of the tourism sector to job creation in West Kalimantan Province remains a critical concern within the context of regional economic development. Despite an increase in the number of tourist attractions, suboptimal management has limited the sector’s ability to generate broad-based economic impacts. Furthermore, the concentration of tourism activities in specific areas has constrained the positive effects of rising tourist arrivals. This study aims to analyze the influence of the number of tourist attractions, the number of tourists, and the number of hotels on employment absorption in West Kalimantan Province during the 2018–2023 period. A quantitative approach was employed using time series secondary data analyzed with EViews 13.0 software. The findings reveal that, partially, the number of tourist attractions has a significant and positive effect on employment absorption, while the number of tourists and hotels have no statistically significant effect. However, when assessed simultaneously, all three variables exhibit a positive and significant impact on employment absorption. These results suggest that comprehensive tourism sector development can serve as a key driver for job creation and regional economic growth. The study’s implications underscore the need to optimize the management of tourist attractions, enhance destination promotion, and strengthen collaboration among government, communities, and private stakeholders to broaden the economic impact of the tourism sector in West Kalimantan.